2013
DOI: 10.1245/s10434-013-3118-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Response and Residual Metastatic Axillary Lymph Node Disease after Neoadjuvant Chemotherapy for Primary Breast Cancer

Abstract: Performance characteristics of AUS, MRI, and PET-CT, while informative, were inadequate to preclude surgical axillary staging of in breast cancer patients after NAC. Whether this information might be used to tailor surgical and postsurgical treatment requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 18 publications
7
74
0
Order By: Relevance
“…The positive predictive value for nodal metastases was reported as 93.1% for nodal ultrasound with core biopsy in a retrospective study of 662 patients with newly suspected breast cancer [14]. It has been suggested that the absence of a fatty hilum on imaging be an indicator for performing biopsy [17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…The positive predictive value for nodal metastases was reported as 93.1% for nodal ultrasound with core biopsy in a retrospective study of 662 patients with newly suspected breast cancer [14]. It has been suggested that the absence of a fatty hilum on imaging be an indicator for performing biopsy [17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Exact cortical measurement on MRI may change depending on positioning, and morphologic nodal change from round to oval may also be affected by patient position. 9 Additionally, there are other technical aspects which may affect MRI analysis of LN response, including respiratory motion artifact from the chest wall and potential false identification of LNs from adjacent vascular structures. 9,24 Hieken used perinodal enhancement to gauge suspicious adenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, there are other technical aspects which may affect MRI analysis of LN response, including respiratory motion artifact from the chest wall and potential false identification of LNs from adjacent vascular structures. 9,24 Hieken used perinodal enhancement to gauge suspicious adenopathy. 9 They demonstrated that ultrasound was the most sensitive method of evaluating the post-NAC axilla, with respective sensitivities of 70% by ultrasound, 63% by position emission tomography (PET), and 61% by MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations